Philosophical Methods in Christian Religious Education: Answering the Challenges of The Alpha Generation Facing the Era of Society 5.0 - Hakh, Irene (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2025)
The era of Society 5.0 builds upon the advancements of the Fourth Industrial Revolution, emphasizing the harmonious integration of technology and human capabilities to address societal challenges. To effectively navigate this era, individuals need to develop critical thinking skills and self-awareness through philosophical methods. These methods, which are particularly relevant for the alpha generation growing up amidst information overload and technological advancements, can be introduced from early childhood. This study aims to introduce philosophical methods within the context of Christian Religious Education to empower the alpha generation in Society 5.0. The research utilizes qualitative methods, specifically a literature review, to propose three philosophical approaches for Christian Religious Education: the critical method, the intuitive method, and the dialectical method. By incorporating these educational philosophies, Christian Religious Education educators can strategize and adapt their teaching approaches to cater to the learning needs of the alpha generation within the framework of Society 5.0.